People With Disabilities In the Pope Francis Document: A Pastoral Guide - Maeja, Jhon Daeng; Setiawan, Charles Virgenius; Kii, Rosalia Ina; Ndung, Yustina (Studia Philosophica et Theologica, 2025)
Disabilities are a term used to replace the term 'disabled'. One of the figures who pays great attention to people with disabilities is Pope Francis. However, the term disability is not yet popular in Indonesia. They are still often discarded and classifiedas weak and marginalized. The purpose of this study is to see Pope Francis' concern for people with disabilities to be a pastoral basis. The research method used is a literature review. The results of the study show that Pope Francis pays special attention to people with disabilities. The pope noted the injustices and rejection that they experienced. The Pope also pays attention to the dignity of disability. The papal documents mention people with disabilities directly. The conclusion of the study is that Pope Francis' concern for people with disabilities can be a pastoral guidance for the Catholic Church in Indonesia